Analisis Biaya Produksi dengan Menggunakan Metode Variable Costing dalam Menentukan Harga Pokok Produksi Per Jenis Produk Pada UD Lyvia Nusa Boga - Miranti Harun; Hendrik Manosoh; Lady Diana Latjandu (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
Production costs are the total of all costs incurred to produce certain goods or services. These costs include the cost of raw materials, labor, marketing, equipment, taxes and overhead costs. The purpose of this study is how to analyze production costs using the variable costing method in determining the cost of production per type of product at UD Lyvia Nusa Boga. The type of research used is qualitative. Data collection techniques using the method of observation, interviews and documentation. Based on the research results, UD Lyvia Nusa Boga still uses a simple method in determining the cost of production. The calculation of the cost of goods manufactured using the company method yields higher results compared to the variable costing method because only variable costs are included in the calculation of the variable costing method.